Using a Boundary Object Perspective to Reconsider the Meaning of STEM in a Canadian Context. Issue 2 (2nd April 2016) - Shanahan, Marie-Claire; Carol-Ann Burke, Lydia E.; Francis, Krista
ABSTRACT: The term STEM, used to describe science, technology, engineering, and mathematics, has come to prominence in Canada over the last decade, raising questions about its meaning. Here we examine its history in the United States and the sociopolitical commitments that have, in parallel, guided science education in Canada. The divergent nature of these histories suggests that STEM may be best viewed as a boundary object, highlighting its value as a collaboration gathering point. This can allow science educators to engage with STEM in ways that are meaningful without necessarily accepting associated definitions and priorities. RÉSUMÉ: L'acronyme STEM, pour parler des sciences, technologies, ingénierie et mathématiques, est devenu populaire au Canada au cours de la dernière décennie, et a soulevé des questions quant à son véritable sens. Nous analysons ici son histoire aux États-Unis, ainsi que les engagements sociopolitiques qui ont parallèlement influencé l'enseignement des sciences au Canada. La nature divergente de ces deux parcours suggère qu'il vaut mieux voir le mot STEM comme un objet limite, et souligner sa valeur comme point de rencontre et de collaboration. Ainsi, les enseignants des sciences pourront participer de façon significative aux disciplines STEM sans nécessairement accepter toutes les définitions et priorités.